DESIGN AND ENERGY PERFOMANCE OF STUDENT BUILDING INTEGRATED WITH PHASE CHANGE MATERIAL IN ASTANA,KAZAKHSTAN - Negmetova, Gulzhan; Yekpyndynova, Nadira; Madenova, Yerkezhan; Abildin, Yerniyaz; Makhin, Bakhytbek (Nazarbayev University School of Engineering and Digital Sciences, 2017)
In this report, student resident building integrated with Phase Change Material (PCM) is designed by “EASY Engineering” Construction Company. The project is designated for Astana city’s residents. The proposed location of the 10-storey building is at the intersection of Turan avenue and 31st street, on the left coast side of the city. This paper contains architectural design of the project, structural analysis, geotechnical design and evaluation of energy performance of the building due to application of PCM.
Keywords: student resident building; student resident; phase change material; architectural design